pengaruh acepromaasin sebagai preanestesi dan sebagai campuran anestetika ketamin terhadap onset dan durasi anestesi pada kucing - , INDAH KARINA, drh. Setyo Budhi, M. P. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aimed to compare the onset and duration of anesthetic combination of ketamine with acepromazine and ketamine which is given after 20 minutes acepromasin giving in cats. Ten male cats were divided into two groups: the first group had been injected by ketamine with acepromasin and the second group were had been injected by ketamine anesthesia after 20 minutes giving acepromasin. Atropine sulfate injected at doses 0.04 mg/kg body weight subcutaneous, twenty minutes later the cat was injected anesthetic combination of ketamine at doses of 15 mg/kg body weight, and acepromasin at doses 0.05 mg/kg body weight for the first group of cats. Second group was injected with atropine sulfate at doses 0.04 mg/kg body weight and then injected acepromasin at doses 0.05 mg/kg body weight, 20 minutes later the cat was injected with the anesthetic ketamine at doses 15 mg/kg body weight. The research variable were onset and duration of anesthesia from each cats, data were analyzed with T-test method. The data obtained were average onset of anesthetic combination of ketamine with acepromasin is 456 seconds and ketamine which is given after 20 minutes acepromazine giving is 324 seconds. Average duration of anesthetic combination of ketamine with acepromasin is 1140 seconds and ketamine which is given 20 minutes after acepromazine giving is 1440 seconds.Analysis results were onset anesthetic combination of ketamine with acepromazine and ketamine which is given 20 minutes after acepromazine giving are significantly different (P <0.05) and duration of anesthetic combinationof ketamine with acepromazine and ketamine which is givenafter 20 minutes acepromazinegiving also significantly different (P <0,05). Based on the result of this research conclude that anesthetic combination of ketamine with acepromazine can be use in surgeries which is needed the short times.